Bidirectional vehicle-to-grid interface under a microgrid project - Leite, V. (2018)
In the emergent deployment of smart grids, storage systems play an important role into assets utilization optimization, providing backup power and peak-shaving. This concept becomes more critical in the context of microgrids with a high penetration of renewable energy resources. Plug-in electric vehicles provide an enormous distributed storage capability, which favours the technical and economical exploitation of such systems. This paper presents a comprehensive implementation and control of a bidirectional power converter for vehicle-to-grid integration, based on a bidirectional DC/DC converter followed by a full bridge DC/AC converter.